2008
DOI: 10.1097/ccm.0b013e31817b8a92
|View full text |Cite
|
Sign up to set email alerts
|

Positive-end expiratory pressure reduces incidence of ventilator-associated pneumonia in nonhypoxemic patients*

Abstract: These findings indicate that application of prophylactic PEEP in nonhypoxemic ventilated patients reduces the number of hypoxemia episodes and the incidence of ventilator-associated pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
92
1
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(101 citation statements)
references
References 34 publications
2
92
1
4
Order By: Relevance
“…First, PAP maintains alveolar pressure and prevents the alveoli from collapsing at the end of expiration and thus improves gas exchange and oxygenation through the recruitment of alveolar units, counterbalance of hydrostatic forces leading to pulmonary edema, and maintenance of airway patency [19][20][21][22] . Particularly in HF patients with pulmonary congestion in whom lung compliance is impaired, PAP induces recruitment of collapsed alveoli, reversal of atelectasis, and induces a fluid shift from the alveoli and the interstitial space to the pulmonary circulation, consequently decreasing the amount of intrapulmonary shunting and improving oxygenation [21,23] .…”
Section: Effect On Respirationmentioning
confidence: 99%
“…First, PAP maintains alveolar pressure and prevents the alveoli from collapsing at the end of expiration and thus improves gas exchange and oxygenation through the recruitment of alveolar units, counterbalance of hydrostatic forces leading to pulmonary edema, and maintenance of airway patency [19][20][21][22] . Particularly in HF patients with pulmonary congestion in whom lung compliance is impaired, PAP induces recruitment of collapsed alveoli, reversal of atelectasis, and induces a fluid shift from the alveoli and the interstitial space to the pulmonary circulation, consequently decreasing the amount of intrapulmonary shunting and improving oxygenation [21,23] .…”
Section: Effect On Respirationmentioning
confidence: 99%
“…[8][9][10]13 However, the study's measurement conditions did not include PEEP or mechanical ventilation, so the benefit of the new cuff in the presence of positive-pressure ventilation is unknown, given that PEEP influences the rate of fluid leak. 9,[12][13][14]16 The selection of a round, inflexible acrylic tube for a trachea model, although common in the literature, 3,8,11 may not translate in vivo, because the most common tracheal cross-sectional shape is an ellipse. 6 Young et al reported that, with an acrylic tube as the trachea model, all the endotracheal tube cuffs tested demonstrated leak, but only 45% of the tubes had a leak when examined in a porcine trachea.…”
Section: See the Original Study On Page 1095mentioning
confidence: 99%
“…2,[7][8][9][10][11] The flow of secretions past the cuff is determined by the height of the column above the cuff, the angle of inclination, the cuff inflation pressure, and the tracheal pressure applied by the ventilator. 9,[12][13][14] The addition of PEEP has been shown, both in vivo and in vitro, to counterbalance this hydraulic force and to limit the leakage past the cuff. 9,13,14 The endotracheal tube and cuff were recently examined for their contributions to VAP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4) Positive end-expiratory pressure (PEEP) ameliorates the hemodynamic state in HF patients through the following mechanisms; reduction of left ventricular (LV) afterload, 5) reduction of LV preload, 6) decrease in work of breathing, and reversal of hypoxia-related pulmonary vasoconstriction. 7) However, the mechanisms by which PEEP improves the respiratory status in HF patients have not been fully elucidated.…”
mentioning
confidence: 99%